FAKTOR PENGETAHUAN WAJIB PAJAK, SISTEM PEMUNGUTAN PAJAK, SANKSI PERPAJAKAN, DAN KUALITAS PELAYANAN PAJAK PADA KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PRIBADI - Diajeng Gumilang (JOURNAL ECONOMICS AND STRATEGY, 2023)
The ability to fulfill all demands increases along with the progress of society, from the upper middle class to the lower middle class. The need for transportation is one of the needs. Having access to transportation is very important because it can promote environmental activities. Motorized vehicles and other means of transportation are no longer seen as a luxury item by the public, but rather as a necessity for getting around and doing daily tasks. This study attempts to determine the relationship between taxpayer compliance with private motorized vehicles and taxpayer understanding, tax collection mechanisms, tax sanctions, and quality of tax services. Literature study is the type of research used. The results of this study indicate that knowledge of taxation, tax collection systems, and tax sanctions have a significant positive effect. While the quality of tax services does not have a significant effect on taxpayer compliance.